Integrated Stem-Pbl Module In Enhancing The Interest And Achievement Towards Genetics Concepts And Critical Thinking Skills - Rahim, Shamimah Parveen Abd (2020)
Scientific and innovative society can be produced by giving priorities in Science, Technology, Engineering, and Mathematics (STEM) as emphasized by Malaysian Higher Education Blueprint (2015-2025). STEM need to be implemented in higher education because universities need to produce competent graduates to support economy growth and sustainable development. Learning STEM through Problem Based Learning (PBL) might allow the undergraduates to become more enthusiastic when problem-based instruction is incorporated with STEM by implementing teamwork and problem-solving techniques to engage the first-year undergraduates fully with the learning. This study was conducted to investigate whether Integrated STEM-PBL module could enhance the interest and achievement towards genetics concepts and critical thinking skills among first-year undergraduates. To develop the Integrated STEM-PBL module, ADDIE instructional design which comprises Analysis, Design, Development, Implementation, and Evaluation phases were used as a framework. A Pre-Experimental research design with one group-posttest design was applied in this study. A total of 50 participants who are first-year undergraduates (second semester) from Faculty of Biology from one of the public universities in Malaysia were involved in this study. To measure the interest towards genetics concepts, this study used the Genetics Interest Questionnaire (GEQ) which was validated by expert with Cronbach’s alpha coefficient for internal consistency reliability measure was 0.979.